1991
DOI: 10.1111/j.1464-410x.1991.tb15419.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilharzial Vesicoureteric Reflux and Bladder Neck Stenosis: Fact or Fiction ?

Abstract: A group of 47 patients with histologically confirmed chronic urinary bilharziasis underwent micturating cystourethrography to look for vesicoureteric reflux (VUR) and bladder neck stenosis (BNS); 13 patients were found to have VUR of varying grades (8 unilateral and 5 bilateral). None had evidence of BNS. Urinary tract infection (UTI), loin pain, hydroureter and renal failure were compared in patients with and without VUR. Of the 13 patients with reflux, 3 had UTI, loin pain was present in 8, 11 had an ipsilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…CT can be used to evaluate the presence of OU and other findings related to chronic schistosomiasis [ 20 ] Garba A 1999 Burkina Faso Transversal study Endemic area residents Ultrasound on 203 children with confirmed infection to detect the presence of OU in children in an hyperendemic area m/f Range: [7–15] The authors only report a prevalence of 2% of OU seen by US. Confirmation of potential role of US as a screening tool for OU [ 36 ] Ibrahim AI 1991 Saudi Arabia Transversal study Endemic area residents Micturating cystourethrogram in 47 patients to study the presence of OU in chronic Schistosomiasis m/f Mean [range]: 34.6 [18–68] Thirteen patients (27%) were found to have OU. Method is no longer of choice by current practices.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…CT can be used to evaluate the presence of OU and other findings related to chronic schistosomiasis [ 20 ] Garba A 1999 Burkina Faso Transversal study Endemic area residents Ultrasound on 203 children with confirmed infection to detect the presence of OU in children in an hyperendemic area m/f Range: [7–15] The authors only report a prevalence of 2% of OU seen by US. Confirmation of potential role of US as a screening tool for OU [ 36 ] Ibrahim AI 1991 Saudi Arabia Transversal study Endemic area residents Micturating cystourethrogram in 47 patients to study the presence of OU in chronic Schistosomiasis m/f Mean [range]: 34.6 [18–68] Thirteen patients (27%) were found to have OU. Method is no longer of choice by current practices.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst 12 studies have used US alone for the diagnosis of OU [ 12 , 19 – 29 ], others have used two methods to confirm the complication (intravenous urography in five case reports [ 30 – 34 ], anterior urography in one patient from a case series [ 33 ], CT scan in one case report [ 35 ]) or an invasive procedure (cystoscopy in one case report [ 35 ]). Very few studies compared the performances of radiological methods: only one study compared the performances of intravenous urography (considered the gold standard) and cystography, finding suboptimal performances of the latter (Sensitivity (Se) 26.8%; specificity (Sp) 66.7%; positive predictive value (PPV) 84.6%; negative predictive value (NPV) 11.8%) [ 36 ]. US proved superior to intravenous urography as one study found better performances (Se 89.5%; Sp 63.6%; PPV 81.0%; NPV 77.8%) and the ability to show hydronephrosis in patients whose kidneys were not visible via intravenous urography [ 37 ].…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…La cistografía evidencia la posible disminución de la capacidad vesical o aparición de defectos de replección que deberán ser evaluados mediante cistoscopia 1, 11,12,16 . La uretrografía retrógrada y miccional nos ayudan a diagnosticar posibles estenosis uretrales y esclerosis de cuello 35 Ciertos estudios defienden el papel de la ecografía en pacientes procedentes de áreas endémicas, teniendo sensibilidad similar a la urografía para la detección de lesiones vesicales, dilataciones ureterales, hidronefrosis y litiasis renales 36 .…”
Section: Figura 1 Corte Ecográfico Transversal De La Vejiga Urinariaunclassified